Systematic Literature Review: Self-Eficacy Matematis Siswa pada Tipe Kepribadian Extrovert dan Introvert dalam Pembelajaran Matematika - Shelly Morin; Dadang Djuandi; Rizki Dwi Siswanto (Universitas Muria Kudus, 2022)
This study aims to identify and describe the type of self-efficacy and personality of extrovert s and introverts. This discussion focuses on the basic theory, definitions, roles that exist at the elementary school, junior high school, high school and college. The research method chosen in this research is a systematic literature study. Collecting data obtained from the Google Schoolar database using the Publish or Perish application. Self-efficacy as self-confidence to be able to complete a task and can improve performance that affects various aspects of life, one of which is in the process of learning mathematics. The type of person seen in several versions depending on the theory of who visited. But basically every human being has one personality type that stands out. The personality type possessed by students can reveal the strengths and weaknesses of the student. So that by knowing one of the personality types possessed by students, teachers can maximize self-efficacy in students to help the mathematics learning process. The results of this study can contribute to further research for researchers who compile research on this issue